2012
DOI: 10.1097/jto.0b013e3182572ead
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemotherapy in Patients With Resected Small-Cell or Large-Cell Neuroendocrine Carcinoma

Abstract: These results suggest that perioperative chemotherapy may be beneficial in patients with resected SCLC or LCNEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
0
24
2
Order By: Relevance
“…Recently, many studies have reported that perioperative chemotherapy may be beneficial in patients with resected LCNEC [32, 36, 37]. Tanaka et al [38] performed a unique study and suggested that perioperative chemotherapy might benefit the survival of patients with LCNEC if the tumors are not immunoreactive to the three neuroendocrine markers evaluated.…”
Section: Surgery For Patients With Lcnecmentioning
confidence: 99%
“…Recently, many studies have reported that perioperative chemotherapy may be beneficial in patients with resected LCNEC [32, 36, 37]. Tanaka et al [38] performed a unique study and suggested that perioperative chemotherapy might benefit the survival of patients with LCNEC if the tumors are not immunoreactive to the three neuroendocrine markers evaluated.…”
Section: Surgery For Patients With Lcnecmentioning
confidence: 99%
“…Certain retrospective reviews of LCNEC patients undergoing surgery have indicated that surgical resection tends to improve overall survival. For such resectable patients, it has been demonstrated that perioperative adjuvant chemotherapy favors survival compared with surgery alone (5,(10)(11)(12). With respect to chemotherapeutic agents, the cisplatin-VP-16 doublet regime has been recommended, similar to the recommendation for patients with SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to chemotherapeutic agents, the cisplatin-VP-16 doublet regime has been recommended, similar to the recommendation for patients with SCLC. This treatment strategy demonstrated satisfactory results in terms of overall survival and recurrence-free survival (11). The majority of previous studies focused on surgically-treated cases due to the difficulty in obtaining a pre-operative pathological diagnosis, therefore, only a small number of studies have evaluated the treatment of advanced LCNEC thus far, including the efficacy of systemic chemotherapy (8,13).…”
Section: Discussionmentioning
confidence: 99%
“…Palliation with radiation may play a role in treatment of unresectable disease [3]. According to Abedalla and colleagues, results suggest that perioperative chemotherapy may be beneficial in patients with resected SCLC and LCNEC [46]. …”
Section: Current Treatment and Prognosis Of Neuroendocrine Tumorsmentioning
confidence: 99%